(untitled) (Asian Journal of Medical and Biological Research, 2021)
Agriculture farmers face abundant risk for crop cultivation at rural area of Bangladesh. About 85% of population in coastal region of Bangladesh, Dumki upazila, related to agriculture for livelihood directly or indirectly. To mitigate the problem facing by the farmers, there are available a lots of climate smart technologies. However, different demographic, socio-economic, production, management and post-harvest determinants influences the adoption of these modern technologies. This study focuses on the identification of farmer’s socio-economic condition, their knowledge, attitude, and perception on improvement of existing livelihood based on selected personal and demographic variables. Both primary and secondary data has been collected from different sources to fulfill the objectives. The results of this study indicated that the farmer’s age, education level and farming experiences significantly influence the adoption of modern technologies. Farmer’s knowledge, perception and attitude differ on different demographic condition like, age, sex, education, farm size, farming year. Results also showed that lacking of quality seeds, lacking/high price of labor and other inputs for crop production hastens the adoption of modern technologies. This study provides some recommendation which might impacts on betterment of farmers’ occupational condition by establishing proper policy and legislation both in local and national level. Asian J. Med. Biol. Res. 2021, 7 (4), 348-358